Key performance indicators : the complete guide to KPIs for business success - Camilleri, Emanuel (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Key Performance Indicators (KPIs) are widely used across organizations. However, are they fully understood in how they can properly shape, improve or even undermine organizational systems and outcomes? This book presents a framework and tools for measuring and managing performance at various levels within an organization, and helps managers re-think the ways to implement KPIs to meet organizational goals. Innovative performance measurement and management is a vital function within any organisation irrespective of its size and industry. Measuring and managing performance (whether on an individual, team or departmental basis) assists management in calibrating their established strategic goals by providing an insight into how well their employees and the organisation are doing and identifying areas of concern for rectification and improvement. This book focuses on the practicality of the performance management tools (for example, Performance Analytics; Performance Reporting; Critical Success Factors; Balanced Scorecard; Benchmarking; Six Sigma; Business Excellence Models; Enterprise Risk Management) and illustrates their use, and the changing nature in relation to how organisational performance will be evaluated in the future. This includes the application of Artificial Intelligence as an important trend in performance measurement and management. Through providing a universal framework for implementing a performance measurement and management system that is applicable to both the private and public sectors, the book is particularly relevant to HR and operational managers and organizational leaders and public administrators at all levels"--
Keywords: Performance standards; Performance -- Management; Organizational effectiveness; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Operations Research